Programmable tuning of graphitic order impacting the perforation of MOF-derived carbon nanostructures for all-purpose high-energy-density supercapacitors - Karim, Golam Masud; Patra, Amalika; Deb, Sujit Kumar; Das, Snehasish; Dutta, Pronoy; Mukherjee, Priyam; Bera, Pranab; Upadhya, Hemanta; V. Dambhare, Neha; Rath, Arup K.; Ghosh, Debasis; Maiti, Uday Narayan (Carbon, 2026)
Precise manipulation of graphitic order in carbon nanostructures and derived materials can be a key strategy to avail their full potential in multifunctional applications; however, it is incredibly challenging to implement on a practical scale. Here, we report a unique programmable pulsed Joule heating (PJH) strategy for the development of graphitization-tunable carbon nanoleaves (GNL) from a metal-organic framework (MOF) and for the precise recovery of graphitic order in GNL after it undergoes pore-forming surface oxidation. A unique electrochemical perforation (ECP) strategy is employed to unzip the graphitic layers of GNLs, thereby removing the in situgenerated fine metal nanoparticles. The adjustable graphitization of GNL by PJH, tunable perforation by ECP, and programmable conductivity recovery by PJH are highly effective in optimizing energy storage performance in supercapacitor devices. As-modified GNLs exhibit an areal capacitance as high as 290.7 mF cm- 2 in aqueous electrolytes, which is 434% higher than that of pristine GNLs. It is this unique combination of a highly accessible surface area, facilitated by ECP, and restored conductivity, achieved by PJH, that drives the exceptional performance boost compared to pristine GNL. The high conductivity and open porosity greatly improved the performance of the water-in-salt (WIS) electrolyte supercapacitor, delivering very high energy density (127.5 mu Wh cm- 2), an extended voltage window (2.3 V), and impressive capacity retention (89%) after 15000 chargedischarge cycles. These ready-to-use binder-free electrodes also exhibit excellent, highly stable performance in wearable asymmetric supercapacitor devices.
Keywords: Electrochemical perforation; Porous graphitic nanostructure; Ultrafast graphitization; Water-in-salt electrolyte; wearable supercapacitor